Human Bone Marrow Mesenchymal Stem Cell (hBMSCs)-Derived miR-29a-3p-Containing Exosomes Impede Laryngocarcinoma Cell Malignant Phenotypes by Inhibiting PTEN - Tingting Yu; Hong Yu; Dong Xiao; Xiangyan Cui (Hindawi Limited, 2022)
Although microRNA-29a-3p was reported to inhibit laryngocarcinoma progression, the potential mechanisms have not been explored clearly. Laryngocarcinoma tissues were collected for analyzing the levels of miR-29a-3p and phosphatase and tensin homolog (PTEN). The miR mimics or inhibitor was transfected into laryngocarcinoma cell lines M4E and Hep2 for the investigation of the biological functions (proliferative, invasion, migratory rates, and apoptotic rates) of this miRNA. The exosomes (Exo) from human bone marrow mesenchymal stem cells (hBMSCs) after the transfection of miR mimics/inhibitor/si-PTEN were isolated and used to stimulate M4E and Hep2 cells. The in vivo mouse model was constructed to verify our findings. The miR-29a-3p level was decreased, and PTEN level was elevated in laryngocarcinoma tissues and the cancer cell lines. MiR mimics could inhibit proliferative, invasive migratory rates while promoting apoptotic rates of M4E and Hep2 cells. MiR-29a-3p was enriched in hBMSC-derived Exo, and the Exo from miR-29a-3p mimics transfected hBMSCs could inhibit laryngocarcinoma cell malignant phenotypes in vitro and prevent tumor progression in vivo. In addition, the direct binding relationship between miR-29a-3p and PTEN in this disease was determined. In conclusion, hBMSC-derived Exo with upregulated miR-29a-3p inhibited laryngocarcinoma progression via regulating PTEN, providing a potential diagnostic and therapeutic target in this disease.